New genus and species of brachypterous planthopper of the tribe Elicini (Hemiptera: Fulgoroidea: Tropiduchidae) from Chile - Campodonico, Juan F. (Zootaxa, 2018)
Selamorpha variegata gen. et sp. nov. is described from Coquimbo Region, Chile. It is characterized by the body dorsally saddle-shaped, brachypterous, tegmina with moderate reticulation, metope elongate, and terga caudally elevated. The new taxon is the second genus of Elicini in Chile and the third of South America. It was found associated with Calceolaria polifolia Hook. (Calceolariaceae).